Effect of heating temperature and time on the formation of volatile organic compounds during reactions between linoleic acid and free amino acids or myofibrillar proteins. (8th October 2022) - Zhou, Tianming; Gao, Haotian; Xing, Baofang; Bassey, Anthony; Yang, Linwei; Li, Chao; Li, Chunbao
Summary: Linoleic acid has been shown as a very important precursor for meat flavour and heating parameters may affect the reaction of linoleic acid with free amino acids (FAAs) or myofibrillar proteins (MPs) and the production of volatile organic compounds (VOCs). This study was aimed to identify the VOCs during heating of linoleic acid only or with FAAs and MPs for different times by gas chromatography‐ion mobility spectrometry (GC‐IMS). Reaction systems were set up to simulate meat, and the transformation pathway of VOCs was tracked by GC‐IMS. Finally, sixty‐two VOCs were identified, of which the content of aldehydes, which had the greatest impact on the aroma of meat, reached the peak (15.94%) when heated to 60 min and then decreased. Principal component analysis (PCA) showed that the effect of heating temperature on the flavour of the system was much greater than that of heating time, and heating at 90 °C for 60 min might be considered to obtain the best flavour. The results showed that FAAs played a critical role in the formation of VOCs that were derived from the oxidation and thermal degradation of linoleic acid, controlling the composition of FAAs may further optimise the flavour of processed meat products. Abstract : Lipid oxidation and thermal degradation are the main sources of flavor in the simulation system, and free amino acids play an important catalytic role. GC‐IMS was used to prove that hydration and retro‐aldol reaction provided a large amount of aldehydes. In addition, it was also found that the effect of temperature was significantly greater than that of time in the formation of flavor.